THE ADMINISTRATION OF THE PENSION REFORM ACT IN THE NON-DOMESTICATED STATES IN NIGERIA THROUGH THE MICRO PENSION PLAN - Ihemadu, Michael C. N.; Imoh, Emmanuel Uchenna (African Journal of Social and Behavioural Sciences, 2025)
Pension plans have become increasingly a discourse in the public space in recent times. The consciousness of the plan has made the private and public sector managers devote attention to how to join their workforce to motivate them to productivity and a safety net after retirement. The most sought-after retirement plan over the globe is the Contributory Pension Plan. Nonetheless, many public sector entities have remained adamant about the benefit scheme retirement plan, especially in the States where Contributory Pension Schemes is not domesticated. To mitigate the financial famine the retirees, go through after retirement, the Micro pension plan becomes a bridge for public servants to take their destinies into their own hands toward contributing part of their earnings to the Contributory Pension Scheme to create an assets buffer for their retirement. This academic paper examines how Public Servants could enrol in the Contributory Pension Scheme without their employer’s side of the contribution. The study uses secondary data techniques and observational methodology. The study concluded by asserting that public Servants of the none non-domesticated Contributory Pension Scheme should make good use of the Micro Pension Plans to address their retirement needs rather than waiting endlessly for unprepared state governments for Contributory Pension Scheme enrolment.